Antibiotic Use by Small‐Scale Farmers for Freshwater Aquaculture in the Upper Mekong Delta, Vietnam. Issue 3 (11th September 2019) - Ström, Gunilla Hallenberg; Björklund, Hanna; Barnes, Andrew C.; Da, Chau Thi; Nhi, Nguyen Huu Yen; Lan, Trinh Thi; Magnusson, Ulf; Norman Haldén, Anna; Boqvist, Sofia
Abstract: This study describes antibiotic use by small‐scale freshwater aquaculture farmers in the upper Mekong Delta in southwestern Vietnam and the knowledge and practices surrounding the cause and prevention of aquaculture disease in that region. Forty five farmers were included in the study, of which 19 (42%) cultivated tilapia Oreochromis spp., 13 (29%) Striped Catfish Pangasianodon hypophthalmus and 13 (29%) giant river prawns Macrobrachium rosenbergii . Antibiotics were used by farmers of tilapia and Striped Catfish (84% and 69% of farmers, respectively), but not by any of the prawn farmers. Most farmers (72%) used antibiotics for around 3 d when treating diseases, depending on the farmers' economic means and whether the fish recovered, as judged by the farmer. If farmers perceived that the antibiotic treatment had failed, the most common response was to change to another type of antibiotic. Some farmers also used antibiotics in the absence of clinical symptoms as a preventive measure. In the absence of rapid, cost‐effective diagnostics, the likelihood for the incorrect use of antibiotics is high, which has implications for antibiotic resistance. Moreover, the sequential use of different antibiotics following therapeutic failure is a risk factor for the emergence of resistance. All farmers that were surveyed were aware of the risks associated with antibiotic use. This may lead to successful intervention toward reduced antibiotic use in freshwater fish farming in Vietnam.